Deconstructing the traditional Japanese medicine "Kampo": compounds, metabolites and pharmacological profile of maoto, a remedy for flu-like symptoms. (December 2017) - Nishi, Akinori; Ohbuchi, Katsuya; Kushida, Hirotaka; Matsumoto, Takashi; Lee, Keiko; Kuroki, Haruo; Nabeshima, Shigeki; Shimobori, Chika; Komokata, Nagisa; Kanno, Hitomi; Tsuchiya, Naoko; Zushi, Makoto; et al.
Abstract Pharmacological activities of the traditional Japanese herbal medicine (Kampo) are putatively mediated by complex interactions between multiple herbal compounds and host factors, which are difficult to characterize via the reductive approach of purifying major bioactive compounds and elucidating their mechanisms by conventional pharmacology. Here, we performed comprehensive compound, pharmacological and metabolomic analyses of maoto, a pharmaceutical-grade Kampo prescribed for flu-like symptoms, in normal and polyI:C-injected rats, the latter suffering from acute inflammation via Toll-like receptor 3 activation. In total, 352 chemical composition-determined compounds (CCDs) were detected in maoto extract by mass spectrometric analysis. After maoto treatment, 113 CCDs were newly detected in rat plasma. Of these CCDs, 19 were present in maoto extract, while 94 were presumed to be metabolites generated from maoto compounds or endogenous substances such as phospholipids. At the phenotypic level, maoto ameliorated the polyI:C-induced decrease in locomotor activity and body weight; however, body weight was not affected by individual maoto components in isolation. In accordance with symptom relief, maoto suppressed TNF-α and IL-1β, increased IL-10, and altered endogenous metabolites related to sympathetic activation and energy expenditure. Furthermore, maoto decreased inflammatory prostaglandins and leukotrienes, and increased anti-inflammatory eicosapentaenoic acid and hydroxyl-eicosapentaenoic acids, suggesting that it has differential effects on eicosanoid metabolic pathways involving cyclooxygenases, lipoxygenases and cytochrome P450s. Collectively, these data indicate that extensive profiling of compounds, metabolites and pharmacological phenotypes is essential for elucidating the mechanisms of herbal medicines, whose vast array of constituents induce a wide range of changes in xenobiotic and endogenous metabolism. Systems biology of traditional medicine: comprehensive analysis of a traditional Japanese medicine, maoto Pharmacological activities of Kampo, or traditional Japanese herbal medicine, are putatively mediated by complex interactions between the plant-derived compounds and endogenous molecules. To elucidate these properties, we performed comprehensive phytochemical profiling, and pharmacological and metabolomic analyses of maoto, an herbal remedy for flu-like symptoms. In the plasma of maoto-treated rats, we detected maoto-derived compounds, metabolites produced from the chemical transformation of maoto compounds by host metabolism and gut microbes, and endogenous metabolites that were appeared following maoto administration. In an acute inflammatory rat model, maoto ameliorated symptoms of sickness behavior, suppressed inflammatory cytokines, and extensively affected common metabolites and lipid mediators. These data suggest that the diverse chemical composition of Kampo broadly affects the host's endogenous metabolism and exerts specific pharmacological effects.